EVALUATION OF THE EFFECT OF ACHYRANTHES ASPERA LINN. (AMARANTHACEAE) IN EXPERIMENTALLY INDUCED INFLAMMATORY BOWEL DISEASE IN RATS. - Bhatt, Pratik kumar A.; Gandhi, Tejal R; Patel, Praful; Patel, Eeknath G.; Trivedi, Upama N. (Asian Journal of Pharmaceutical Research and Development, 2013)
To Evaluation of the Effect of Achyranthes Aspera Linn. (Amaranthaceae) In Experimentally Induced Inflammatory Bowel Disease In Rats. Healthy S.D rats (200-250gm, 12-14 weeks, either sex) were randomly allocated to 6 groups (n=6): Animals of Group I, Group-IV, Group-V & Group-VI were given water, 5-ASA (100mg/kg), MeAa (200mg/kg) & MeAa (400mg/kg) respectively once a day orally for 18 days. On 11th day of the study, Colitis was induced by DNBS (120mg/kg in 50% ethanol) in animals of Group-III-VI, on same day Group II received 50% ethanol (1.6ml/kg) intracolonically. On 18th day, the animals were weighed and anaesthetized with chloroform and sacrificed for Physical, histological, Biological, as well as Histopathological parameters. Methanolic extract of drug Achyranthes Aspera Linn.was previously proved for its effect as anti inflammatory, anti microbial, anti-oxidant as well as drug was reported to contain three major constituent which was also proven their activity against NFκB, a main causative activator found in IBD. DNBS Model control animals showed significantly induce as well as increase the severity of Chronic inflammation of IBD, while Pretreatment with 5- ASA, MeAa significantly reversed these changes induced by DNBS and proving their activity against IBD. Thus Methanolic extract of Achyranthes Aspera Linn. Significantly reduce the severity of the IBD induced by DNBS in rats and the protective activity might be attributed to anti-inflammatory and anti-oxidant activities of drugs as well as they might be act on NFκB activity.